The Impact of the Marble Running Game on Rough Motor Abilities of Early Childhood - Didik Purwanto (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. The primary concern addressed in this research study is the persistent deficiency in children's gross motor skills, indicating a need for improvement. The researcher aims to delve into the impact of playing marbles on the enhancement of children's gross motor skills. Materials and Methods. The research methodology employed in this study involved a quantitative experimental approach. The study focused on 12 children in group B, 6 boys and 6 girls. Data was gathered through observation, documentation, and interviews. The analysis involved the use of percentage and t-test methods. Upon reviewing the comparisons made before and after therapy, it was found that the average levels of various attributes such as balance, speed, and flexibility demonstrated notable changes. Results. Based on the t-test results, the t-table value is 1.79588. The computed t-value is 9.530, with a significance level of 0.000, indicating that the observed effect of the running marbles game on improving gross motor abilities in young children is statistically significant (sig < 0.05). Conclusion. After analysis, the null hypothesis (HO) is rejected, while the alternative hypothesis (Ha) is accepted. This suggests that engaging in playing marbles has a discernible impact on the development of gross motor skills in children between the ages of 5 and 6 years.